Clinical relevance of glycosylation in triple negative breast cancer: a review - Chakraborty, Mrinmoy; Kaur, Jasmine; Gunjan; Kathpalia, Meghavi; Kaur, Navkiran (Glycoconjugate journal, 2024)
Glycosylation alterations in TNBC have significant implications for tumor behavior, diagnosis, prognosis, and therapeutic strategies. Dysregulated glycosylation affects cell adhesion, signaling, immune recognition, and response to therapy in TNBC. Different types of glycosylation, including N-linked glycosylation, O-linked glycosylation, glycosphingolipid glycosylation, mucin-type glycosylation, and sialylation, play distinct roles in TNBC. The “barcoding” method based on glycosylation sites of the membrane type mannose receptor (MR) shows promise in accurately distinguishing breast cancer subtypes, including TNBC. Alpha-L-fucosidase 1 (FUCA1) and Monocarboxylate transporter 4 (MCT4) have been identified as potential diagnostic and prognostic markers for TNBC. The glycosylation status of PD-L1 impacts the response to immune checkpoint blockade therapy in TNBC. Inhibiting fucosylation of B7H3 enhances immune responses and improves anti-tumor effects. Targeting glycosylated B7H4 and modulating estrogen metabolism through glycosylation-related mechanisms are potential therapeutic strategies for TNBC. Understanding the role of glycosylation in TNBC provides insights into disease mechanisms, diagnosis, and potential therapeutic targets. Further research in this field may lead to personalized treatment approaches and improved outcomes for TNBC patients.